Предмет: Алгебра,
автор: kdapost2015
Нужны более менее подробные решения
Приложения:
Ответы
Автор ответа:
0
Ответ:
↓↓↓↓↓↓↓↓↓↓↓↓↓↓↓↓
Объяснение:
f(x)=-3x+2
f( )=-3x+2=-2+2=0
f(-3)=-3*(-3)+2=11
f(-x)=-3*(-x)+2=3x+2
-f(x)=- (-3x+2)=3x-2
f(2x)=-3*2x+2=-6x+2
f(x-2)=-3(x-2)+2=-3x+8
f(x²)=-3x²+2
(f(x))²=(-3x+2)²=(2-3x)²=4-12x+9x²
f(x-2)²=-3(x-2)²+2=-3(x²-4x+4)+2=-3x²+12x-10
(f(-x²)-1)²=(-3(-x²)+2 -1)²=(3x²+1)²=9x⁴+6x+1
f(-x³)=-3(-x³)+2=3x³+2
f(2x³)=-3(2x³)+2=-6x³+2
f ((2x)³)=-3(2x)³+2=-24x³+2
( f(2x) )³=(-3(2x)+2 )³=(-6x+2)³=(2-6x)³=8-72x+216x²-216x³
Похожие вопросы
Предмет: Русский язык,
автор: evstratiev0909
Предмет: Английский язык,
автор: latuta4
Предмет: Русский язык,
автор: e1488kx
Предмет: Математика,
автор: milinato
Предмет: Химия,
автор: nummiik